PELAKSANAAN PROGRAM PELATIHAN KERJA OLEH UNIT PELAKSANA TEKNIS LATIHAN KERJA (UPT-LK) WILAYAH I PROVINSI RIAU - Malau, Brian Aredo; ", Mayarni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Vocation training program by Vocation Training Technical Organizer (UPT-LK) Unit Region I Riau Province is a program with a purpose to train workers to be competent, productive, and resourceful through different kinds of courses available for job seekers and unemployed. This training program is centered in Pekanbaru and has been ongoing since 1983, but the implementation is having a number of problems and obstacles. The purpose of this research is to analyze the implementation of the training program and the factors that influence it.Theory used in this research is training components theory by Moekijat which are training participants, instructors, time, training materials and methods. This research used descriptive qualitative method, and data collecting methods are observation, interviews, and documentation.Keywords: Implementation, Program, Vocation Training